The Role of Natural Rent in the Economic Development of Kazakhstan - JANSHANLO, Ramzan Esarovich (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The rent relations are the most important element of all system of the economic relations, represent the complex, constantly becoming complicated phenomenon. They have gained special multi-purpose practical value in the conditions of modern multistructure economy. The question of equitable distribution and assignment of investment incomes needs to be considered with a possibility of his most effective use for the benefit of all society. The state is capable to restore equivalent cost proportions at an interindustry exchange, by means of the legislative levers. The considered conceptual provisions assume increase of a role of the state concerning, first of all, rent branches. The natural rent is one of sources and levers of economic recovery today.